Comparison between rectus sheath block with 0.25% ropivacaine and local anesthetic infiltration with 0.5% ropivacaine for laparoscopic inguinal hernia repair in children - Tamura, Takahiro (Nagoya J Med Sci, 2019)
This randomized, observer-blinded prospective study aimed to compare the postoperative analgesic effects of ultrasound-guided rectus sheath block with those of local anesthetic infiltration of the surgical field in children undergoing inguinal hernia repair. Children aged 2 to 14 years, scheduled for elective single-incision laparoscopic percutaneous extraperitoneal closure, were randomly allocated to receive ultrasound-guided rectus sheath block (group R) or local anesthetic infiltration of the surgical field (group L). In group R, 0.5 ml/kg of 0.25% ropivacaine (per side) was administered after intubation. In group L, 0.4 ml/kg of 0.5% ropivacaine was administered after peritoneal closure. Postoperative pain was assessed using the Face Scale and Face, Legs, Activity, Cry, Consolability scale at various time points, including the primary endpoint of 2 h after leaving the operation room. Additional analgesic drugs were used according to the Face Scale scores. Patient characteristics, the amount of additional drugs, and complication rate were evaluated in both groups. The patient and surgical characteristics were comparable between groups. The Face Scale and Face, Legs, Activity, Cry, Consolability scale scores were not significantly different between group R (n = 38) and group L (n = 38) at 2 h after leaving the operation room. The amount of additional drugs administered at 2 h after leaving the operation room were also comparable between groups. Our findings suggest that the postoperative analgesic efficacy of ultrasound-guided rectus sheath block is not superior to that of local anesthetic infiltration of the surgical field for pediatric single-incision laparoscopic percutaneous extraperitoneal closure.